Short Communication: Dye-yielding plant resources of Maharashtra, India: A checklist - SONALI HINDURAO PATIL; DILIP DAMODAR KURLAPKAR; DATTATRAYA KRISHNA GAIKWAD (Biodiversitas Journal of Biological Diversity, 2019)
Patil SH, Kurlapkar DD, Gaikwad DK. 2019. Dye-yielding plant resources of Maharashtra, India: A checklist. Biodiversitas 20: 250-266. Natural dyes have rich variation in sources of dyestuff and possess superior aesthetic quality, which is more pleasing to the eye due to unique natural color. Because of their nontoxic effect, they are used for coloring textile, cosmetics, drugs, and various food products. Although indigenous knowledge system has been practiced over the years in the past, the use of natural dyes has diminished over generations due to lack of documentation. Also, there is not much information available on databases of either dye-yielding plants or their products. Therefore, the purpose of the present study was to document the dye yielding plant species and associated knowledge from the study area. Present study provides the first comprehensive checklist of dye yielding Angiosperms of Maharashtra and their resulting color, pigment, and distribution have also been reported. A checklist consists of 195 species distributed among 153 genera and 58 families are presented based on published literature on dye plants, various state and regional floras.